2013
DOI: 10.1007/s13142-013-0197-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple behavior interventions to prevent substance abuse and increase energy balance behaviors in middle school students

Abstract: This study examined the effectiveness of two transtheoretical model-tailored, computer-delivered interventions designed to impact multiple substance use or energy balance behaviors in a middle school population recruited in schools. Twenty middle schools in Rhode Island including sixth grade students (N=4,158) were stratified and randomly assigned by school to either a substance use prevention (decreasing smoking and alcohol) or an energy balance (increasing physical activity, fruit and vegetable consumption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
84
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(87 citation statements)
references
References 57 publications
3
84
0
Order By: Relevance
“…Researchers have concluded that multiple simultaneous behavior change interventions are promising for addictive behaviors and for multiple cancer prevention behaviors including diet, physical activity, and obesity prevention [18][19][20][21][22][23][24]. In this Special Section, Velicer et al [25] describe a large intervention trial that examined the effectiveness of two different computer-delivered interventions designed to influence multiple behaviors in middle school students: The first intervention targeted multiple substance use behaviors; the other targeted energy balance behaviors. The energy balance intervention was found not only to have an impact on the intended energy balance behaviors but also, unexpectedly, on the substance use prevention behaviors.…”
mentioning
confidence: 99%
“…Researchers have concluded that multiple simultaneous behavior change interventions are promising for addictive behaviors and for multiple cancer prevention behaviors including diet, physical activity, and obesity prevention [18][19][20][21][22][23][24]. In this Special Section, Velicer et al [25] describe a large intervention trial that examined the effectiveness of two different computer-delivered interventions designed to influence multiple behaviors in middle school students: The first intervention targeted multiple substance use behaviors; the other targeted energy balance behaviors. The energy balance intervention was found not only to have an impact on the intended energy balance behaviors but also, unexpectedly, on the substance use prevention behaviors.…”
mentioning
confidence: 99%
“…The sample size in the studies varied from 71 to 5,407 (average = 1,349) participants, and included male and female participants. The average age ranged from 25, 8 to 75 years, with the exception of two studies which samples were composed by preadolescents (26) and adolescents (25) (Table II). The main inclusion criterion for the studies was the presence of an aggravating factor, such as overweight (9,10,18,20,22,27), high blood pressure (12), increased risk of cardiovascular diseases (20), and diabetes mellitus (11).…”
Section: Methodological Characteristics Of the Studiesmentioning
confidence: 99%
“…The predominant design was the randomized clinical trial (5)(6)(7)(8)(9)(10)(11)(12)14,20,22,26,28), but studies of interventions without a control group (CG) (18,26), an experimental (1) and quasi-experimental (24) group were also identified. Only 8 studies clearly described the randomization method used (10,12,14,20,22,(26)(27)(28).…”
Section: Methodological Characteristics Of the Studiesmentioning
confidence: 99%
“…perceived benefits and perceived risks) of engaging in a behavior 28,29,31 . The TTSS is based on Bandura's Self-Efficacy model 32 and models of behavior maintenance 33 . This instrument assesses the degree to which an individual feels tempted to engage in a target behavior, as well as his or her confidence to abstain from this behavior, regardless of being in difficult or risky situations 32,33 .…”
Section: Current Studymentioning
confidence: 99%
“…The TTSS is based on Bandura's Self-Efficacy model 32 and models of behavior maintenance 33 . This instrument assesses the degree to which an individual feels tempted to engage in a target behavior, as well as his or her confidence to abstain from this behavior, regardless of being in difficult or risky situations 32,33 . These measures have shown to be important mediator variables for various TTM-based health behavior interventions [27][28][29][30] .…”
Section: Current Studymentioning
confidence: 99%